Theories of the policy process - Weible, Christopher M.; Sabatier, Paul A. (Westview Press, 2017)
"A comprehensive primer to the major contemporary theoretical frameworks used in policy process research written by leading public policy scholars"--
Literaturangaben
Westview ist ein Imprint von Routledge, Taylor & Francis seit 2017
Keywords: Aufsatzsammlung; Theorie; Planung; Politik; Strategie